Ligand dynamics controlled reverse spin cross over in bis pyrazolyl pyridine based Fe(II) complex cation with metallodithiolato anions with an example of a ferromagnetic 2:1 cocrystal of mixed Ni(III)/Ni(II) oxidation states - Manoharan, Periakaruppan T.; Sambandam, Balaji; Amsarani, Ramamoorthy; Varghese, Babu; Gopinath, Chinnakonda S.; Nomura, Kiyoshi (Inorganica Chimica Acta, 2011)
We report here the crystal and molecular structures of three compounds [FeL(2)] [Ni(mnt)(2)] (1), [FeL(2)](2) [Ni(mnt)(2)](3)center dot 2H(2)O (2) and [FeL(2)] [Cu(mnt)(2)]center dot 2CH(3)CN (3) where L = 2,6-bis(3,5-dimethylpyrazol-1-ylmethyl) pyridine and mnt = maleonitriledithiolate, and their detailed spectroscopic and magnetic properties using variable temperature Mssbauer, EPR, susceptibility studies, along with room temperature electron spectroscopy for chemical analysis (ESCA) studies. The observed temperature dependant high spin/low spin (HS/LS) ratios of [FeL(2)](2+) cations in these lattices, exhibiting `reverse spin cross-over' measured unequivocally by Mssbauer, have been interpreted as resulting from differing amount of `void space' in the lattice, a measure of the ease of lattice dynamics originating from ligand L. Differential scanning calorimetric data points this HS/LS transition to order-disorder type of second order phase transitions. While trying to test this lattice dynamics controlled property of [FeL(2)](2+) cations an unusual behavior of cocrystallization of two planar complex anions of the same type in two different oxidation states, viz. [Ni(mnt)(2)](2) and [Ni(mnt)(2)] , was observed in [FeL(2)](2+) [Ni(mnt(2))](3), supported by crystallography, ESCA chemical shifts of Ni 2p(3/2) and EPR. The susceptibility data in combination with ESCA chemical shifts of S 2p(3/2) and Ni 2p(3/2) on all the compounds reveal the importance of charge transfer between the two counter ions. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Iron complexes; Magnetism; Reverse-spin crossover; X-ray crystal structures

Computational survey of ligand properties on iron(III)-iron(II) redox potential: exploring natural attenuation of nitroaromatic compounds - Rizvi, Masood Ahmad; Mane, Manoj; Khuroo, Mohammad Akbar; Peerzada, Ghulam Mustafa (Monatshefte Fur Chemie, 2017)
This study is a computational investigation of the ligand effect on the redox potential of iron redox couple aimed at screening these systems for novel applications. The influence of common and naturally available organic compounds with diverse ligand characteristics (nature of donor site, chelation, pre-organization, degree of back acceptance) on the redox potential of iron(III)-iron(II) redox couple has been theoretically calculated using an appropriate level of density functional theory (DFT). The DFT calculated redox potentials of iron complexes are explored to supplement, corroborate, and predict the experimental behavior of the studied systems towards environmental reduction of nitroaromatic compounds to corresponding anilines. The comparative avidity of iron complexes with cysteine derivatives for the reduction of nitroaromatic compounds has been theoretically explored and based on structure-activity relationship; new iron complexes with a range of reactivity and enhanced ability towards nitroaromatic reduction have been predicted.
Keywords: Catechol derivatives; computational chemistry; Density functional theory; Iron complexes; Ligand effect on redox potential; Natural attenuation; Nitroaromatic compounds